1986
DOI: 10.2170/jjphysiol.36.177
|View full text |Cite
|
Sign up to set email alerts
|

Hypercapnic and hypoxic ventilatory responses during growth.

Abstract: Cross-sectional studies on hypercapnic and hypoxic ventilatory chemosensitivities were performed in 71 children ranging in age from 7 to 18 yrs. The subjects were classified into 6 successive 2-year age groups. CO2 ventilatory response was measured by rebreathing 5 % CO2 in Oz, a slight modification of the method originally proposed by Read. The results were evaluated when the C02-ventilation feedback control system was supposed to have attained the open-loop condition. Hypoxic ventilatory response was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Results range from an increased ventilatory response to hypoxia in 5–17‐year‐old children compared with adults (Marcus et al., ) to no difference among children and adolescents from 7–18 years of age (Honda et al., ). One reason for the different results may be the different scaling factors used ranging from body weight to lean body mass, body surface area or pulmonary function (Honda et al., ; Marcus et al., ). As HVR is a ventilatory control parameter expressing V E by degree of hypoxia, it makes sense to use vital capacity as scaling factor, which adjusts for the different lung volumes that can potentially be utilized to reach V E (Rowland, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results range from an increased ventilatory response to hypoxia in 5–17‐year‐old children compared with adults (Marcus et al., ) to no difference among children and adolescents from 7–18 years of age (Honda et al., ). One reason for the different results may be the different scaling factors used ranging from body weight to lean body mass, body surface area or pulmonary function (Honda et al., ; Marcus et al., ). As HVR is a ventilatory control parameter expressing V E by degree of hypoxia, it makes sense to use vital capacity as scaling factor, which adjusts for the different lung volumes that can potentially be utilized to reach V E (Rowland, ).…”
Section: Discussionmentioning
confidence: 99%
“…HVR in children even at LA has not been widely examined and results are controversial. Results range from an increased ventilatory response to hypoxia in 5–17‐year‐old children compared with adults (Marcus et al., ) to no difference among children and adolescents from 7–18 years of age (Honda et al., ). One reason for the different results may be the different scaling factors used ranging from body weight to lean body mass, body surface area or pulmonary function (Honda et al., ; Marcus et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence that the ventilatory response to hypoxia is dependent on age is mixed. Using an isocapnic progressive hypoxic technique, no differences in the hypoxic ventilatory response was noted from 7 to 18 years of age (Honda et al 1986). In contrast, using the same isocapnic rebreathe technique, Marcus et al (1994) reported a significantly increased hypoxic ventilatory response in children compared to adults; however, the relationship with age was weak (r = 0.34).…”
Section: Introductionmentioning
confidence: 94%
“…Using an isocapnic progressive hypoxic technique, no differences in the hypoxic ventilatory response was noted from 7 to 18 years of age (Honda et al. ). In contrast, using the same isocapnic rebreathe technique, Marcus et al.…”
Section: Introductionmentioning
confidence: 99%
“…Although Marcus et al [5] corrected their subject's ventilatory responses for body surface area, the coefficient of variation of the corrected ventilatory response to hypoxia was still 50%. Similarly, Honda et al [6] reported that coefficient of variation values for body surface area-corrected hypoxic ventilatory responses ranged from 63–81% in children aged 7–12 years (see their Table 1). These data suggest strongly that body surface area may not adequately correct the ventilatory response for body size in young children.…”
Section: Introductionmentioning
confidence: 89%